Case reportsCardiac arrest during percutaneous coronary intervention in a patient ‘resistant’ to clopidogrel – successful 50-minute mechanical chest compression - Protasiewicz, Marcin; Szymkiewicz, Pawel; Sciborski, Krzysztof; Orda, Alina; Karolko, Bozena; Jonkisz, Anna; Lebioda, Arleta; Mysiak, Andrzej (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
We report a case of 72-year-old female patient with end-stage chronic kidney disease, undergoing percutaneous coronary intervention (PCI) that resulted in a cardiac arrest caused by a thrombus mediated flow limitation in the left coronary artery. With mechanical cardiopulmonary resuscitation (CPR) PCI of the left main artery was performed successfully during 50 min cardiac arrest. The patient was discharged from the hospital without compromising cardiac function and neurological deficits.